Optimization of virtual reality (vr) technology based on active deep learner experience (adlx) in increasing student learning independence in islamic education subjects and ethics in school - Siti Khoiriyah; Ahmad Shofiyuddin; Mowafg Abrahem Masuwd (At Turots: Jurnal Pendidikan Islam, 2025)
This research is motivated by the urgency to enhance students' learning independence in Islamic Religious Education and Character Education in the digital era, where conventional learning methods are often less effective. The objective of this research is to optimize the use of Virtual Reality (VR) technology based on Active Deep Learner Experience (ADLX) to improve the learning independence of ninth-grade students on the theme of Islamic propagation by Wali Songo in Java. The research results indicate that the integration of VR and ADLX through systematic planning, implementation, and assessment stages successfully creates immersive and personalized learning experiences, enhances students' conceptual understanding, and fosters self-regulation and intrinsic motivation. Active collaboration between teachers and parents also proves to support the improvement of students' learning independence, making this approach an effective model in PAI and Character Education in the digital age